Transition States in Protein Folding (Communications in Computational Physics, 2018)
The folding dynamics of small single-domain proteins is a current focus ofsimulations and experiments. Many of these proteins are 'two-state folders', i.e. proteinsthat fold rather directly from the denatured state to the native state, without populatingmetastable intermediate states. A central question is how to characterize theinstable, partially folded conformations of two-state proteins, in particular the rate-limitingtransition-state conformations between the denatured and the native state.These partially folded conformations are short-lived and cannot be observed directlyin experiments. However, experimental data from detailed mutational analyses of thefolding dynamics provide indirect access to transition states. The interpretation ofthese data, in particular the reconstruction of transition-state conformations, requiressimulation and modeling. The traditional interpretation of the mutational data aimsto reconstruct the degree of structure formation of individual residues in the transitionstate, while a novel interpretation aims at degrees of structure formation of cooperativesubstructures such as α-helices and β-hairpins. By splitting up mutation-induced freeenergies into secondary and tertiary structural components, the novel interpretationresolves some of the inconsistencies of the traditional interpretation.